Communicating About Chronic Caregiving in the Workplace: Employees' Disclosure Preferences, Intentions, and Behaviors. Issue 1 (2nd January 2016) - White, Zachary M.; Wills, Jeremiah B.
Abstract : A growing number of Americans are living with chronic health conditions that require informal, ongoing care from family members who are also in the paid labor force. In this exploratory study, communication privacy management is used to make sense of chronic caregiving ( N = 48–64) and noncaregiving ( N = 174–178) employees' disclosure preferences, intentions, and behaviors in the workplace. We find that workers in general anticipate that they would disclose to many individuals at work about their caregiving, but employees actually disclose much less information to far fewer people at work when they occupy the chronic caregiver role. For chronic caregivers, positive perceptions about coworker supportiveness predict increased disclosure behaviors. Finally, future research directions as employers, workers, and policy makers prepare for the complex challenges associated with negotiating paid work and unpaid chronic caregiving are provided.